1987
DOI: 10.1111/j.1469-8137.1987.tb00866.x
|View full text |Cite
|
Sign up to set email alerts
|

Water Relations of Coconut Palms Affected With Root (Wilt) Disease

Abstract: SUMMARYThe water relations of apparently healthy and root (wilt)-diseased coconut palms {Cocos nucifera L.) were investigated. Leaves of diseased palms had lower stomatal resistances (with relatively high transpiration rates) and leaf water potentials than apparently healthy palms. Although there was a small reduction of osmotic potential in leaves of diseased palms, there was almost complete loss of turgor potential, and Haccidity resulted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 5 publications
2
9
0
Order By: Relevance
“…By contrast, stomata of palms suffering from root (wilt) disease remained open throughout the day regardless of the season (Rajagopal et al ., 1986). Leaf water potentials were also less in diseased plants (down to −1.99 MPa) leading to flaccidity (Rajagopal et al ., 1987). Progressive stomatal closure (from 10:00 to 12:00 hours) was also observed by Kasturi Bai et al .…”
Section: Plant Water Relationsmentioning
confidence: 99%
“…By contrast, stomata of palms suffering from root (wilt) disease remained open throughout the day regardless of the season (Rajagopal et al ., 1986). Leaf water potentials were also less in diseased plants (down to −1.99 MPa) leading to flaccidity (Rajagopal et al ., 1987). Progressive stomatal closure (from 10:00 to 12:00 hours) was also observed by Kasturi Bai et al .…”
Section: Plant Water Relationsmentioning
confidence: 99%
“…Application of balanced dose of fertilizer along with organic manure application and irrigation has favoured the growth and development of the palms and reduced intensity of root (wilt) symptoms. Rajagopal et al (1986a and1987b) have reported that, leaves of diseased palms had lower stomatal resistance (with relatively high transpiration rates) and leaf water potentials than apparently healthy palms. Diseased palms also indicated that dysfunction of stomatal regulation and there was abnormally wide stomatal opening.…”
Section: Nut Yield and Copra Contentmentioning
confidence: 99%
“…Wilt, scorch, blight, and other diseases associated with xylem dysfunction disrupt water transport capacity, causing substantial morbidity and mortality of plants (Beckman et al 1962; Rajagopal et al 1987; Denny et al 1990; Aguirreolea et al 1995; Lorenzini et al 1997). Denny et al (1990) determined that transpiration decreased as wilt symptoms appeared by weighing mock-inoculated and Ralstonia -infected tomato plants to measure water loss and estimate whole-plant transpiration rates.…”
Section: Discussionmentioning
confidence: 99%